The Concept of the Person as “Subject” and “Place” of Morality According to Paul Ricoeur - Sobkowiak, Jarosław (Studia Theologica Varsaviensia, 2020)
e concept of the subjectivity of a person presented in this article has shown that man as a subject appears in constant references and relations in which his existence is embedded. On the one hand, it escapes the determinism of nature, on the other hand, it reveals a certain crack between its nature and action. is leads to the conclusion that even if a person is characterised by individuality, it is not a separate existence. It seems justified to return to the question of what makes a person, in spite of both external and internal variability; they remain the same or otherwise what builds and what destroys the subjectivity of the person? e question thus posed reveals the first threat to human subjectivity which is the fact of the existence of evil. For it is not only something external to man but also something that makes man both the “place” of the appearance of evil and responsible for evilB8. While staying in Ricoeur’s philosophy characterised by a dialectical movement one can already see in the language discussing evil a threat to certain “deposits of hope” present in his thoughtB<. For the religious language to which Ricoeur ultimately reduces the problem of evil is the language of hope and eschatology. Freedom also takes on a new meaning in this context. It is no longer just something that has been enslaved but above all something that is a “desire for the possible.” A possible freedom is the Resurrection. In this perspective, even evil and suffering can find their ultimate meaning, and the subjective character of morality does not threaten to fall into subjectivism. Moreover, it is in the name of such subjectivism that morality demands for the subject this “otherness,” the hope that comes from the Resurrection.